Impact of pre-drying and frying time on physical properties and sensorial acceptability of fried potato chips - Cruz, G. (2018)
ABSTRACT In this work the effects of pre-drying and frying time on colour, oil, texture and sensorial acceptability (overall liking) of potato chips were evaluated. Potato chips were pre-dried for 0, 10, 20 and 30 min at 60 °C and fried in soybean oil at 190 °C for 60, 70 and 80 s. The colour parameters (L*, a* and b*) increased or decreased depending on the pre-drying and frying time. Hardness increased as the pre-drying and frying time increased. On the other hand, the water initially removed by pre-drying decrease the gradient of mass transfer (water–oil). The oil content reduced to (about 21%) in pre-dried samples when compared to control sample. Finally, sensorial evaluation showed that samples without pre-drying and/or fried for very short or very long times had low acceptance levels. The pre-drying and frying times influenced the colour, texture, water and oil content, and resulted into fried potato chips with better acceptance scores.